2006
DOI: 10.1088/0967-3334/27/12/009
|View full text |Cite
|
Sign up to set email alerts
|

Resonance sensor measurements of stiffness variations in prostate tissuein vitro—a weighted tissue proportion model

Abstract: Prostate cancer is the most common type of cancer in men in Europe and the US. The methods to detect prostate cancer are still precarious and new techniques are needed. A piezoelectric transducer element in a feedback system is set to vibrate with its resonance frequency. When the sensor element contacts an object a change in the resonance frequency is observed, and this feature has been utilized in sensor systems to describe physical properties of different objects. For medical applications it has been used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 23 publications
2
76
0
Order By: Relevance
“…Moreover, the presence of benign conditions that are stiffer than normal tissue, e.g. glandular BPH and calcifications [43,44], increases the number of detected false positives, although BPH and calcifications may be visualized on B-scan and, therefore, excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of benign conditions that are stiffer than normal tissue, e.g. glandular BPH and calcifications [43,44], increases the number of detected false positives, although BPH and calcifications may be visualized on B-scan and, therefore, excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups (Dunn and Silver 1983;Hof 2003;Huang et al 2005;Klein et al 2005;Kuo et al 2001;Lally et al 2004;Provenzano et al 2002;Silver et al 2001;Suki et al 1994;Wu et al 2003) have reported findings on mechanical properties of some soft tissues, but most of their studies were focused on tendons, ligaments, cartilage, skin, muscles, lungs or arteries. In contrast, just a few publications (Jalkanen et al 2006a(Jalkanen et al , 2006bKrouskop et al 1998;Phipps et al 2005aPhipps et al , 2005bYang et al 2006) presented quantitative results on prostate tissue stiffness. Krouskop et al (1998) investigated the mechanical properties of normal and diseased prostate tissues with displacement loading experiments.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed cancerous tissue had a measurable elevated Young's modulus compared with normal tissue in the same gland. Jalkanen et al (2006b) measured the stiffness of prostate tissues with a piezoelectric resonance sensor. Subsequently, they related their measurements to tissue morphology and concluded that cancer greatly increases the measured stiffness (Jalkanen et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown in previous studies and indicates the potential for several biomedical applications [2,3,4,5]. For example, studies on prostate tissue show the possibility to differentiate between benign and malignant prostate tissue [6]. In a study where a resonance sensor probe was attached to a counter balance arm, the measured frequency shift was evaluated on silicone discs and prostate tissue [7].…”
Section: Introductionmentioning
confidence: 55%